2020
DOI: 10.17263/jlls.759252
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Social Networking Sites for Reinforcing the Linguistic Competence of EFL Learners

Abstract: The unprecedented progress in digital appliances nowadays resulted in increasing reliance on the use of technology, which facilitated construction of knowledge including the acquisition of languages (Thorne, 2010). Formal education has developed drastically and neither educators nor classroom input is perceived as the only source of information; unlimited resources exist for learners to construct knowledge (Benson, 2007). Online applications foster learners' autonomy and independence and encourage them to prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…These thirty articles revealed that there are five groups of targeted subjects that are of interest to researchers. A significant sum of studies was performed on the tertiary education level learners with 19 articles contributing to the list [30,31,35,36,[38][39][40]43,45,46,[48][49][50][51][52][53][54][55]58]. Five articles were directed towards the response from educators [33,34,42,56,57].…”
Section: N/a /mentioning
confidence: 99%
See 4 more Smart Citations
“…These thirty articles revealed that there are five groups of targeted subjects that are of interest to researchers. A significant sum of studies was performed on the tertiary education level learners with 19 articles contributing to the list [30,31,35,36,[38][39][40]43,45,46,[48][49][50][51][52][53][54][55]58]. Five articles were directed towards the response from educators [33,34,42,56,57].…”
Section: N/a /mentioning
confidence: 99%
“…Five articles [36,38,41,49,50] have researched the assimilation of Facebook in formal English learning whereas only one article [42] employed Facebook for informal English learning. About a third of the total articles reviewed [29,35,37,39,40,45,46,48,[51][52][53]57] have not specified any SNS platform in the research, indicating that a lot of studies were done to investigate the influence of SNS as a whole on learning rather than just a single platform. Instagram may be regarded as the second most popular medium for informal learning, with two articles [43,47] devoted to the topic, but just one article [58] focused on its application in formal learning.…”
Section: Rq 1: What Are the Types Of Social Networking Sites (Sns) Pl...mentioning
confidence: 99%
See 3 more Smart Citations